Expression of LATS1 in head and neck squamous cell carcinoma and its effect on tumor cell proliferation and invasion: Expression of LATS1 in head and neck SCC - Wan, Wuhanhui; Sun, Baochun; Yang, Shuzhi; Zhou, Chengyong; Li, Yanni (Cellular and Molecular Biology, 2022)
Nowadays, the incidence and mortality of head and neck tumors are gradually increasing. Head and neck malignant tumors (such as laryngeal cancer, hypopharyngeal cancer, oral cancer, nasopharyngeal cancer, oropharyngeal cancer, and other head and neck malignancies) are more common among systemic tumors. The most common pathological head and neck tumor type is squamous cell carcinoma, accounting for about 90%. In this study, immunohistochemical methods were used to collect the normal squamous epithelial tissues of the head and neck, atypical hyperplasia tissues, and head and neck squamous cell carcinomas on a tissue chip for detection. The recombinant LATS1 overexpression plasmid was prepared and transferred into B88 cells. Western blotting, MTT, and Transwell chamber methods were used to detect the effects of LATS1 proliferation, migration, and B88 cell overexpression. The experimental results showed that in head and neck squamous cell carcinoma, the expression of LATS1 protein decreased from 59.3% to 11.3%. At the same time, this protein inhibited the proliferation, migration, and invasion of head and neck squamous epithelial cells and also inhibited epithelium- Interstitial transformation exerts its tumor suppressor effect, indicating that LATS1 may play a tumor suppressor effect as a tumor suppressor gene. An in-depth study of the role and mechanism of LATS1 protein in the occurrence of head and neck squamous cell carcinoma may provide new opportunities for the treatment of head and neck squamous cell carcinoma in the future.